Optimal location of service centres under uncertain costs - Klapita, Vladimir; Svecova, Zuzana (Communications - Scientific letters of the University of Zilina, 2004)
It is fairly questionable to estimate future costs in the problems of strategic decision. The uncertainty may cause that a resulting solution could be very inefficient considering current costs. In this report we try to find an approach, which enables to determine a unique solution of a location problem under uncertain costs so that the solution be resistant to future changes. We deal with a sensitivity analysis and with a connection of an exact mathematical programming method and the theory of fuzzy sets.